Uji GPS Tracking Dalam Skala Transportasi Antar Kota - Iftitahatul Hanifah; Bambang Nurcahyo Prastowo (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2016)
The accuracy level of a system in order to obtain an accurate data. Each tool has a different level of accuracy as well as to the accuracy of tracking system. This tracking system is used to locate a vehicle. It is usually using GPS tool to obtain position data in coordinate point.A GPS tracking testing system is constructed in this research to see positional data obtained from the GPS. Two GPS were used, a cn06 GPS as test GPS and GPSmap 76CSx as secondary data. Obtained data will be selected in coordinates, time, and speed. Selection of data is using regular expression in PHP. These data will later be displayed in the form of maker and web using Google Maps. The analysis will be done by comparing two markers that have adjacent time of retrieval.The result of this research shows that the factor that affect the difference in the accuracy of GPS is the speed of the vehicle. Other obstructing factors such as multi-storey building and large trees will have no effect if the speed is keep at constant pace. In this intercity testing, the result is similiar to previous study, that the important factor is the speed.